2017
DOI: 10.7759/cureus.960
|View full text |Cite
|
Sign up to set email alerts
|

Radiological and Functional Outcome of Displaced Colles’ Fracture Managed with Closed Reduction and Percutaneous Pinning: A Prospective Study

Abstract: Background: Displaced Colles’ fractures are treated by manipulation and below elbow cast application. Malunion is a common complication, resulting in pain, mid-carpal instability, and post-traumatic arthritis. Fracture stabilization by percutaneous pinning is a simple, minimally invasive technique that helps prevent displacement of the fracture, thereby minimizing complications. This study aims to assess the amount of collapse after closed manipulation and percutaneous pinning with Kirschner wires (K-wires) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…This finding corroborates with the finding of venkatesh RR et al [11] So K -wire fixation group has better and statically significant anatomical reduction. This finding is supported by the work of Panthi s et al and stein AHJr et al [13,14] . We have observed that there was significant difference in the range of movement in two group which is supported by the work of Mohamaed F et al and Venkatesh RB et al [11,15] Range of movement like palmer flexion, dorsal flexion, supination and pronation, ulnar deviation and redial deviation are significantly better in K-wire fixation group.…”
Section: Discussionsupporting
confidence: 71%
“…This finding corroborates with the finding of venkatesh RR et al [11] So K -wire fixation group has better and statically significant anatomical reduction. This finding is supported by the work of Panthi s et al and stein AHJr et al [13,14] . We have observed that there was significant difference in the range of movement in two group which is supported by the work of Mohamaed F et al and Venkatesh RB et al [11,15] Range of movement like palmer flexion, dorsal flexion, supination and pronation, ulnar deviation and redial deviation are significantly better in K-wire fixation group.…”
Section: Discussionsupporting
confidence: 71%
“…Among these, 0.5 mm, 1 mm and 2 mm collapse of radial inclination was seen in 51.11 percent, 13.33 percent and 2.22 percent of the patients respectively. Panthi et al [14] , in their study, made radiographic measurements using a goniometer to assess the amount of collapse. The preoperative mean dorsal angle and the mean ulnar variance were 22.33 and 3.66, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This is a metaphyseal fracture of the distal radius that typically occurs 2.5cm proximal to the carpal articulation which presents with dorsal displacement and angulation as well as radial shortening of the distal radial fragment ( Panthi et al 2017 ). This fracture pattern is classically described on lateral plain film X-rays of the wrist as a ‘Dinner Fork’ deformity and is associated with an ulnar styloid fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, Colles’ fractures are low energy, intra-articular and extra-articular distal radius fractures which occur due to a fall on the extended wrist. Colles’ fracture and similar variations are the most common fracture of the distal radius in adults ( Panthi et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%